Simulation of Digital Control of Human Arm Based PSO Algorithm in Virtual Reality - Z. Al-Faiz, Mohammed; A .Ali, Abduladhem; H.Miry, Abbas (Journal of Engineering and Sustainable Development, 2012)
Soft computing research is concerned with the integration of artificial intelligent tools in a complementary hybrid framework for solving real world problems. This paper tries to explore the potential of using soft computing methodologies in control of plant (human arm),utility and effectiveness of soft computing approaches for the control of seven degree of freedom of human arm with structured is presented. It presents a PID tuning method that uses a Particle Swarm Optimization (PSO) as a main gain of PID tuning using multi objective to improve the time response of system such settling time and overshoot. The method implements in the 3D space using Virtual Reality (VR) to compare between the proposed tuning rules and the traditional tuning rules under disturbance load . MATLAB Ver.2009a software is used to show the efficiency of the proposed tuning rule. Simulation results demonstrate that better performance can be achieved with this method relative to 1) trial and error tuning 2)Ziegler-Nichols tuning 3)conventional tuning.